Hubungan Aceh-Turki Usmani dalam Bustan al-Salatin - Rozali, Ermy Azziaty (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2010)
In 16 century, the sultanate Aceh under the Sultan Alauddin Riayat Syah al-Kahhar requested Ottoman as a powerful Islamic state in that time. Among the significant record wich refersto historical event, committed by al-Raniri in his 'magnum opus' Bustan al-Salatin. The Bustan al-Salatin record on Aceh-ottoman relation became benchmark to the further assistant request by following malay leaders. There is another sources, such as manuscript Tarikh Bandar Aceh Darussalam and Hikayat Meukota Alam which noted the same event and probably referring to the Bustan al-Salatin.